Pelatihan Pembuatan Media Ajar Quiziz dan Komic Digital dengan Aplikasi Comic Life 3/5/15 Full Version Bagi Guru Paud, Taman Kanak-Kanak, dan Sekolah Dasar - Setyorini, Nurul; Khabib Sholeh; Suryo Daru Santoso; Kadaryati; Umi Faizah (JPM: Jurnal Pengabdian Masyarakat, 2023)
Educational media has become a crucial tool that teachers need to provide in the teaching process, particularly in the current era of digital disruption. One relevant option for instructional media is digital comics. Digital comics hold the potential to be an effective and engaging learning tool. This study aims to conduct training on using instructional media in the form of Quizizz and digital comics through the Comic Life application in versions 3, 5, and 15. The methodology involves approaches such as lectures, discussions, and demonstrations. The activities take place at Wilcambidik Ngombol Elementary School, Purworejo Regency, targeting 30 teachers from PAUD (early childhood education), TK (kindergarten), and SD (elementary school) levels in the Wilcambidik Ngombol area. The challenges faced are the limited skills of teachers in developing innovative instructional media like digital comics and interactive quizzes. To address this, the proposed solution is to organize training on using Comic Life versions 3, 5, and 15, as well as Quizizz, for PAUD, TK, and SD teachers in the region. Furthermore, resource support and mentoring will be provided to enhance the development of innovative instructional media. This engagement activity encourages the participation of teachers from various school levels to enhance their understanding of utilizing digital comic media and the Quizizz platform. Preliminary analysis results indicate unmet needs in instructional media development. After participating in training involving experts like Dr. Khabib Sholeh, Mr. Suryo Daru Santoso, and Nurul Setyorini, participants demonstrated improved understanding and skills in digital literacy, utilizing the Quizizz platform, and implementing the Comic 2 Lite approach in the teaching process.